Setup for meV-resolution inelastic X-ray scattering measurements and X-ray diffraction at the Matter in Extreme Conditions endstation at the Linac Coherent Light Source - Mcbride, E. E.; White, T. G.; Descamps, A.; Fletcher, L. B.; Appel, K.; Condamine, F. P.; Curry, C. B.; Dallari, Francesco; Funk, Stefan; Galtier, E.; Gauthier, Maxence; Goede, S.; et al. (Review of Scientific Instruments, 2018)
We describe a setup for performing inelastic X-ray scattering and X-ray diffraction measurements at the Matter in Extreme Conditions (MEC) endstation of the Linac Coherent Light Source. This technique is capable of performing high-, meV-resolution measurements of dynamic ion features in both crystalline and non-crystalline materials. A four-bounce silicon (533) monochromator was used in conjunction with three silicon (533) diced crystal analyzers to provide an energy resolution of similar to 50 meV over a range of similar to 500 meV in single shot measurements. In addition to the instrument resolution function, we demonstrate the measurement of longitudinal acoustic phonon modes in polycrystalline diamond. Furthermore, this setup may be combined with the high intensity laser drivers available at MEC to create warm dense matter and subsequently measure ion acoustic modes. Published by AIP Publishing.
CRIS-Team WoS Importer:2020-01-15